Meningkatkan Kemampuan Kognitif Anak Usia 4-5 Tahun pada Angka Menngunakan Media Gelas Angka - Marliana Novita Sari; Sunaryo Sunaryo; Erna Risnawati (Merpsy Journal, 2025)
This study aims to enhance the cognitive abilities of Group A children aged 4–5 years at TK ABA Purwodadi, Purwodadi District, Purworejo Regency in the 2024/2025 academic year, particularly in understanding numerical concepts through the use of “number cup” media. The research employed a Classroom Action Research (CAR) model consisting of four stages: planning, implementation, observation, and reflection. A qualitative descriptive approach was used to explore the meaning, process, and impact of instructional actions implemented to improve children’s learning outcomes. The study was conducted over two cycles, and data were collected using observation sheets.The research subjects were 22 children aged 4–5 years, comprising 9 boys and 13 girls. The findings indicate a significant improvement in children’s cognitive mastery of numbers 1–10. During the pre-cycle stage, only 18% (4 children) demonstrated adequate understanding. This increased to 41% (9 children) in Cycle I. Following adjustments made to address challenges identified in Cycle I, Cycle II showed a further improvement, reaching 77% (17 children). These results demonstrate that the use of number cup media effectively enhances young children’s ability to understand numerical concepts. Additionally, the media contributed to increased interest and motivation in learning numbers among Group A children at TK ABA Purwodadi.